The state of scientific research on the use of specialist knowledge in smuggling investigations - Yu. Yu. Kovalov (Bulletin of Kharkiv National University of Internal Affairs)
The article substantiates that smuggling as a socially dangerous phenomenon has existed since the inception of the first state formations. Its emergence was facilitated by the desire to avoid paying customs duties and moving goods beyond the control of state authorities. It is established that in order to counteract smuggling, appropriate legal measures were introduced in different historical periods. It is emphasised that today the criminal offences related to smuggling include smuggling of cultural property, poisonous, potent, explosive substances, radioactive materials, weapons or ammunition (except for smooth-bore hunting weapons or ammunition), parts of rifled firearms, and special technical means of covertly obtaining information; smuggling of timber and valuable tree species; smuggling of goods (except for excisable goods and electricity); smuggling of excisable goods; smuggling of narcotic drugs, psychotropic substances, their analogues or precursors or counterfeit medicines.